ANALISIS TUGAS KEPALA DESA MENURUT PASAL 26 AYAT 1 UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA DAN FIQH SIYASAH (STUDI KASUS DI DESA NAGRAK KECAMATAN DARANGDAN KABUPATEN PURWAKARTA, JAWA BARAT) - Darussalam, Badar; Rahim, Abdur (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
In creating good governance in accordance with applicable regulations, cooperation between the village head and the community is needed in creating shared welfare, and there is a need for supervision from the community over the village head to control the movements of the village head, so that the village head knows what the village head is tasked with. in administering village government and the village head knows what the main need of the village community itself is, so as to create good governance. The purpose of this research is to know and understand the Duties of the Head of Nagrak Village, Darangdan District, Purwakarta Regency According to Law Number 6 of 2014 concerning Villages. As well as the duties of the head of Nagrak Village, Darangdan District, Purwakarta Regency, according to Fiqh Siyasah. This research is qualitative research. Data collection technique carried out by means of field research, using the observation method, and interviewing the Village Head, Village Secretary, Bamusdes, Babinsa and Rw in Nagrak Village, Darangdan District, Purwakarta Regency, totaling five informants. The duties of the Head of Nagrak Village, Darangdan District, Purwakarta Regency According to Law Number 6 of 2014 concerning Villages, have been going quite well but not optimally, this is due to several factors including the lack of cooperation between the village government and the village community which has resulted in gaps between the two, lack of community knowledge related to the duties of the village head. In terms of Siyasah Fiqh, in its implementation in Nagrak Village, there are those that are appropriate and not appropriate, this is caused by the condition of the territory and the legal system in Indonesia which uses statutory law